Iron therapy as treatment of anemia: A potentially detrimental and hazardous strategy in colorectal cancer patients. (January 2018) - Wilson, M.J.; Harlaar, J.J.; Jeekel, J.; Schipperus, M.; Zwaginga, J.J.
Abstract: In colorectal cancer patients, iron therapy, and especially intravenous iron therapy, is increasingly used to treat anemia and reduce the use of blood transfusions. However, iron has also been shown to be an essential nutrient for rapidly proliferating tissues and cells. In this respect, anemia of inflammation, characterized by limited duodenal iron uptake and sequestration of iron into the reticuloendothelial system, might be regarded as a potentially effective defense strategy of the human body against tumor growth. We therefore hypothesize that iron therapy, by supporting colorectal tumor growth and increasing the metastatic potential, may worsen tumor prognosis in colorectal cancer patients. This hypothesis is particularly supported for colorectal cancer by laboratory, epidemiological and animal studies, demonstrating the role of iron in all aspects of tumor development growth. Compared to non-malignant colon cells, tumor cells differ in the levels and activity of many iron import and export proteins, resulting in an increase in intracellular iron level and enhanced proliferation. In addition, it is demonstrated that iron is able to amplify Wnt signaling in tumors with Apc mutation, a critical mutation in the development of colorectal cancer. If our hypothesis is to be confirmed, current practice of iron administration, as treatment for anemia and as replacement of blood transfusions, can be hazardous and should be completely reconsidered.